Effect of Alkali Treatment Duration on Tensile and Flexural Properties of Pineapple Fiber Composites (Ananas comosus) - Ricky Kurniawan; Edi Widodo; Ali Akbar; Mulyadi Mulyadi; Sulis Yulianto; Dewi Sartika (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
Pineapple leaf fiber is a natural fiber with high cellulose content, making it a promising reinforcement for polymer composites. This study introduces novelty by systematically analyzing the effect of varying 5% NaOH alkali soaking durations (2, 4, 8, 16, and 24 hours) on the tensile and flexural properties of unidirectional pineapple fiber-reinforced polyester composites a range and comprehensive comparison not extensively explored previously. Composites with a 30% fiber volume fraction were fabricated using the hand lay-up method. Tensile and three-point bending tests were conducted according to ASTM D638 and D790, respectively. Results indicated that a 24-hour alkali treatment yielded the highest tensile strength of 44.82 MPa with a strain of 0.1080%, suggesting optimal fiber-matrix adhesion. Conversely, the highest flexural strength of 122 MPa and a modulus of 14,616 MPa were achieved after 16 hours of soaking. Therefore, the optimal alkali treatment duration depends on the targeted mechanical property: 24 hours for maximum tensile strength and 16 hours for optimal flexural performance. These findings aid in enhancing the mechanical properties of pineapple fiber composites through controlled alkali treatment, with potential applications in lightweight automotive panels, interior components, and sustainable construction materials where a balance between tensile and flexural properties is crucial.